Covid-19, occupational social distancing and remote working potential in Ireland - Frank Crowley; Justin Doran (University College Cork, Spatial and Regional Economic Research Centre (SRERC), 2020)
The Covid-19 pandemic has had a sudden and drastic impact on labour supply and output In Ireland. As the Irish government responds, a key question is how covid-19 will impact people and places differently. There is considerable uncertainty around the implications of social distancing measures and remote working for the Irish labour market. The objective of this paper is to get a better understanding of the social distancing and remote working potential at an occupational, sector and regional level in Ireland. We generate two indices which capture the potential impact of Covid-19 through identifying (i) the occupations which may have the most potential to engage in social distancing procedures and (ii) the occupations which may have the most scope for remote working. This is accomplished using occupational level data from O*NET which provides very detailed information of the tasks performed by individuals with their occupations. The paper identifies that social distancing and remote working potential differs considerably across occupations, sectors and places. Examples of large employment which have relatively high indices are teaching occupations at secondary and third level and programme and software developers. While occupations which have large employment but which possess relative low indices are nurses and midwives and care workers. The potential for social distancing and remote work favours occupations located in the Greater Dublin region and provincial city regions. At a town level - more affluent, more densely and highly populated, better educated and better broadband provisioned towns have more jobs with greater potential for social distancing and remote working.
Keywords: 330